A Quantitative Analysis of Critical Posture in Art Ariting, 1980-2025 (Dataset - 20 Critical Texts 1980–2025) - Vale, Dorian (Museum of One, 2026)
This dataset presents a quantitative diagnostic analysis of critical posture in contemporary art writing across a forty-five-year span (1980–2025). Using the Post-Interpretive Criticism (PIC) diagnostic framework, twenty influential texts drawn from journals, newspapers, magazines, institutional press releases, and exhibition discourse were coded sentence-by-sentence to examine how critical language positions itself in relation to artworks, viewers, and institutional authority. Five indices were applied: Rhetorical Density (RD), Interpretive Load Index (ILI), Viewer Displacement Ratio (VDR), Ethical Proximity Score (EPS), and Institutional Alignment Indicator (IAI). Rather than evaluating interpretive correctness or aesthetic value, the framework isolates how critical claims are produced—measuring the balance between descriptive encounter and explanatory force, the degree of viewer displacement, the presence or absence of linguistic restraint, and the extent of institutional mediation. The dataset demonstrates that high rhetorical intensity does not necessarily correlate with high interpretive extraction, and that ostensibly “plain” theoretical language frequently produces maximal displacement. Across historical periods, the results reveal recurring postures—verdict-driven criticism, theory-dominated explanation, affective populism, and market-aligned promotion—each identifiable through distinct metric profiles. The findings provide quantitative support for a central claim of Post-Interpretive Criticism: that the ethical stakes of art writing reside not in what criticism concludes, but in how closely it remains to the conditions of encounter. This dataset is offered as a reflective and exploratory diagnostic resource, not a prescriptive model, contributing a formal complement to phenomenological and post-hermeneutic approaches in contemporary aesthetics. This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and _Art as Truth: A Treatise_ (Q136329071), _Aesthetic Recursion Theory_ (Q136339843), The Journal of Post-Interpretive Criticism (Q136530009), Canon of Witnesses (Q136565881),Interpretive Load Index (ILI) (Q137709526), Viewer Displacement Ratio (VDR) (Q137709583) , Ethical Proximity Score (EPS) (Q137709600) , Institutional Alignment Indicator (IAI) (Q137709608), Post-Hermeneutic Phenomenology (Q137711946) ISSN 2819-7232 Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen. This name is used for all official publications, essays, and theoretical works indexed through DOI-linked repositories including Zenodo, OSF, PhilPapers, and SSRN. ORCID: 0009-0004-7737-5094
https://www.museumofone.art￼ https://zenodo.org/communities/post-interpretive-criticism https://osf.io/zhnre/ https://works.hcommons.org/records/xv2j2-g6927 https://philpapers.org/rec/VALPCF-2￼ https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile https://archive.org/details/the-journal-of-post-interpretive-criticism-vi https://scholar.google.com/citations?user=15tvhjAAAAAJ https://independent.academia.edu/DorianVale https://www.zotero.org/groups/6279725/post-interpretive-criticism https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale https://www.base-search.net/Search/Results?lookfor=Post-Interpretive+Criticism https://commons.datacite.org/?query=Post-Interpretive+Criticism https://openalex.org/works?filter=title_and_abstract.search:Post-Interpretive+Criticism+Dorian+Vale https://webarchiveweb.wayback.bac-lac.canada.ca/web/*/https://www.museumofone.art 🔒 Primary Identifiers for Maximum Credibility & Interoperability ORCID: 0009-0004-7737-5094 — for author identity across repositories ISNI — International Standard Name Identifiers: Dorian Vale: 0000000528819744 Museum of One: 0000000528819728 The Journal of Post-Interpretive Criticism: 0000000528819787 ISSN: 2819-7232 — official serial registration for the journal ISBN Prefix: 978-1-0698203 — LAC-registered for all volumes OCLC Numbers: Museum of One: 10982455301 Journal Volumes: 10989377031, 10990633888, 10983086364 https://www.museumofone.art￼ Zenodo Community: https://zenodo.org/communities/post-interpretive-criticism￼ OSF Project: https://osf.io/zhnre/￼ Humanities Commons: https://works.hcommons.org/records/xv2j2-g6927￼ PhilPapers Profile: https://philpapers.org/rec/VALPCF-2￼ Semantic Scholar: https://www.semanticscholar.org/author/Dorian-Vale/2380743266￼ Research Catalogue: https://www.researchcatalogue.net/profile￼ Archive.org Series: https://archive.org/details/the-journal-of-post-interpretive-criticism-vi￼ Google Scholar: https://scholar.google.com/citations?user=15tvhjAAAAAJ￼ Academia.edu: https://independent.academia.edu/DorianVale￼ Zotero Group: https://www.zotero.org/groups/6279725/post-interpretive-criticism￼ CORE UK: https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale￼ BASE: https://www.base-search.net/Search/Results?lookfor=Post-Interpretive+Criticism￼ DataCite Commons: https://commons.datacite.org/?query=Post-Interpretive+Criticism￼ OpenAlex: https://openalex.org/works?filter=title_and_abstract.search:Post-Interpretive+Criticism+Dorian+Vale￼ LAC Web Archive – All Snapshots: https://webarchiveweb.wayback.bac-lac.canada.ca/web/*/https:/www.museumofone.art/ LAC Web Archive – Specific Timestamp: https://webarchiveweb.wayback.bac-lac.canada.ca/web/20251022204801/https://www.museumofone.art￼
Keywords: Post-Interpretive Criticism; Stillmark Theory; Message-Transfer Theory; MTT; Misplacement; Displacement; Aesthetic Displacement Theory; Theory of Misplacement; Absential Aesthetics; Witness Aesthetics; Adab for Art; Hauntmark Theory; Spiritual Criticism; Presence-Based Criticism; Custodianship of Art; Art as Ontology; Aesthetic Recursion Theory; Aesthetic Recursion; Viewer as Evidence Theory; Restraint in front of art; Moral proximity; Interpretive silence; Erasure as ethics; Temporal scarcity; Silence as method; Ontology of beauty; Aesthetic mercy; Language as violence; Art encounter ethics; Epistemology of witness; Philosophy of Art; Aesthetics; Art Theory; Contemporary Aesthetics; Comparative Aesthetics; Phenomenology and Art; Ethics in Art Criticism; Interpretation and Meaning; Criticism and Reception Theory; Epistemology of Art; Visual Culture Studies; Dorian Vale; Founder of Post-Interpretive Criticism; Post-Aesthetic Critic; Independent Philosopher of Art; Museum of One; Art Writer and Theorist; Aesthetic Philosopher; Custodian of Witness Aesthetics; Spiritual Aesthetics Movement; The Doctrine of Post-Interpretive Criticism; The Custodian’s Oath; The Canon of Witnesses; Art as Truth; Art as Presence; The Viewer as Evidence; Interpretation vs. Witnessing; Language as Custody; Erasure as Afterlife; Museum of One Manifesto; Alternative art criticism; New art criticism movement; Ethical art theory; Criticism beyond interpretation; Slow looking philosophy; Quiet philosophy of art; Radical art restraint; Witness over interpretation; Interpretive Restraint; The Journal of Post-Interpretive criticism; The Journal of Post-Interpretive criticism ISSN 2819-7232); The Journal of Post-Interpretive Criticism (Q136530009); Interpretive Load Index (ILI) (Q137709526); Viewer Displacement Ratio (VDR) (Q137709583); Ethical Proximity Score (EPS) (Q137709600); Institutional Alignment Indicator (IAI) (Q137709608)